Analysing Implementation Of Balance Score Card To Front Office Department At Adiwana Unagi Suites 2022 - Agus Bisena, I Kadek; Yogi Susana, Kadek (Journal of Comprehensive Science, 2023)
The success of a company is influenced by the performance of the departments in its organization. For this reason, the company must be able to measure and evaluate the staff performance. One of the famous tools to measure and manage the performance of the department and staff is KPI based on the Balance Score Card. Adiwana Unagi Suites, a boutique resort in Ubud has implemented a Balance Score Card in its 2022 business process. The research method is executed by using descriptive analysis study. The result of the performance shows some clues that the management and the department itself must discuss the measurement again, especially in customer related. The result also showed us that there was a lack of consistency from the front office team in doing the duty especially in attending training